Kinematic Evolution of the Southern North Atlantic: Implications for the Formation of Hyperextended Rift Systems. Issue 1 (6th January 2018) - Nirrengarten, M.; Manatschal, G.; Tugend, J.; Kusznir, N.; Sauter, D.
Abstract: We focus on the southern North Atlantic rifted margins to investigate the partitioning and propagation of deformation in hyperextended rift systems using plate kinematic modeling. The kinematic evolution of this area is well determined by oceanic magnetic anomalies after the Cretaceous normal polarity superchron. However, the rift and early seafloor spreading evolution (200–83 Ma) remains highly disputed due to contentious interpretations of the J magnetic anomaly on the Iberia‐Newfoundland conjugate margins. Recent studies highlight that the J anomaly is probably polygenic, related to polyphased magmatic events, and therefore does not correspond to an isochron. We present a new palinspastic restoration without using the J magnetic anomaly as the chron M0. We combine 3‐D gravity inversion results with local structural, stratigraphic, and geochronological constraints on the rift deformation history. The restoration of the southern North Atlantic itself is not the primary aim of the study but rather is used as a method to investigate the spatiotemporal evolution of hyperextended rift systems. We include continental microblocks that enable the partitioning of the deformation between different rift segments, which is of particular importance for the evolution of the Iberia‐Eurasia plate boundary. Our modeling highlights the following: (1) the segmentation of the Iberia‐Newfoundland rift system during continental crust thinning, (2) the northward V‐shape propagation of mantle exhumation and seafloor spreading, (3) the complex partitioning of deformation along the Iberia‐Eurasia plate boundary, and (4) a three‐plate propagation model which implies transtension. Key Points: Prebreakup and early seafloor spreading kinematic model of the southern North Atlantic Segmentation of the Iberia‐Newfoundland rift system occurred during thinning Mantle exhumation and seafloor spreading occurred via V‐shape propagation